255 THE ROLE OF GERIATRIC MEDICINE IN CARE OF OLDER ADULTS WITH MAJOR TRAUMA. (25th October 2022) - Rafferty, M; Murphy, D; Cloney, T; Brent, L; Dukelow, T; Ahern, E
Abstract: Background: In recent Major Trauma Audit Reports the most common cause of major trauma is low falls, 46-49% of injured patients were aged over 65. These are an important group to identify and to prioritise for geriatrician led MDT care. There is currently no specialist geriatric medicine service in Ireland for older adults with major trauma. We aimed to evaluate patients with major trauma currently co-managed by orthopaedic surgery and geriatric medicine, the role of geriatric medicine and the potential role of a major trauma geriatric service. Methods: We reviewed local data collected for the Irish Hip Fracture Database to examine the incidence of major trauma presenting in older adults and the role of geriatric medicine. We included patients who had injuries in addition to hip fracture including radius, ulna, clavicle, humerus, rib, vertebra, pelvis fracture subdural haemorrhage, diffuse brain injury and traumatic subarachnoid haemorrhage. Results: In 2020, there were 437 older adults admitted with hip fractures and likely 2185 patients presenting with fragility fractures. We identified 32(7%) patients who sustained other major injuries in addition to hip fracture. Nationally, these patients have a higher in-hospital mortality (11% v 5%). All of these patients had comprehensive geriatric assessment (CGA) and geriatrician-led MDT care. These patients are at high risk for poorer outcomes; delirium, pressure ulcers, hospital acquired infection and disability, prolonged length of stay, delayed transfers of care, premature institutionalisation and death. Conclusion: There is a role for expansion of proactive early identification and geriatric medicine input for all older adults with major trauma, in addition to those with hip fractures and other injuries. The increased mortality in these patients has not previously been published. International evidence supports early intervention from a specialist geriatric medicine service, with CGA to provide exceptional, continuous and co-ordinated care.